ADJECTIVE SUFFIXATION AND STYLISTIC MEANING IN FRANZ KAFKA’S THE METAMORPHOSIS - Palqi Wijdani; Nurholis Nurholis; Toneng Listiani (Universitas Islam Sumatera Utara (UISU), 2026)
This study examines adjective-forming suffixation in Franz Kafka’s The Metamorphosis by integrating derivational morphological analysis with stylistic interpretation. The study aims to identify the types and frequencies of adjective-forming suffixes and to explore their contribution to the novel’s thematic and stylistic construction. Employing a qualitative descriptive approach supported by quantitative frequency analysis, the data were collected from the English translation of The Metamorphosis and analyzed using theories of derivational morphology proposed by Katamba (2018), Plag (2018), and related scholars. The analysis identified 73 valid instances of adjective-forming suffixation distributed across eighteen suffix types. The most productive suffixes were -ful (13 instances), -al (8 instances), -y (7 instances), and -less (6 instances). The findings indicate that most derived adjectives function as qualitative adjectives, describing emotional states, psychological conditions, and physical characteristics, while relational adjectives primarily establish social and contextual relationships. The distribution of suffixes reveals a significant increase in adjective use in the final chapter, corresponding to the intensification of Gregor Samsa’s psychological decline and social isolation. Furthermore, suffixes such as -ful and -less contribute to the representation of suffering, vulnerability, powerlessness, and alienation, which constitute central themes of the novel. The study concludes that adjective-forming suffixation functions not only as a productive morphological process but also as a stylistic resource that supports characterization, thematic development, and meaning construction in literary discourse.